2003
DOI: 10.1029/2003gl017240
|View full text |Cite
|
Sign up to set email alerts
|

Coherence of Antarctic sea levels, Southern Hemisphere Annular Mode, and flow through Drake Passage

Abstract: It is known from small sets of tide gauges that sub‐surface pressure (sea level corrected for the inverse barometer effect) around Antarctica varies coherently around about half of the continent, and that this coherent signal is related to atmospheric forcing in the form of the Antarctic Oscillation, or Southern Hemisphere Annular Mode. We here confirm that this coherence extends to a more extensive network of tide gauges, and to parts of the continental shelf far from the shore, as measured by bottom pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
125
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(140 citation statements)
references
References 9 publications
15
125
0
Order By: Relevance
“…The background colouring is bottom depth, in metres. 1999; Hughes et al, 2003]. It will be seen below that this extends to seasonal and interannual timescales also.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The background colouring is bottom depth, in metres. 1999; Hughes et al, 2003]. It will be seen below that this extends to seasonal and interannual timescales also.…”
Section: Methodsmentioning
confidence: 99%
“…Strong circumpolar coherence in transport has been demonstrated using data from various Antarctic tide gauges and bottom pressure recorder (BPR) deployments [Aoki, 2002;Hughes et al, 2003]. It has also been demonstrated that this subseasonal transport variability is forced (with undetectable lag) by the varying circumpolar eastward winds associated with the Southern Annular Mode (SAM; ).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…[2] Analysis of tide gauge and bottom pressure recorder (BPR) data has shown that oceanic subsurface pressure (SSP; sea level corrected for the ''inverse barometer effect'') and bottom pressure vary coherently around Antarctica on timescales from intraseasonal to interannual, coincident with changes in the oceanic circumpolar transport [Aoki, 2002;Hughes et al, 2003;Meredith et al, 2004]. Surface westerly (easterly) wind anomalies around the Southern Ocean close to Antarctica accelerate (decelerate) the oceanic circumpolar transport, associated with a fall (rise) in SSP and bottom pressure at the edge of the continent itself.…”
Section: Introductionmentioning
confidence: 99%